One-Chip Integration of MEMS-Tunable VCSELs Operating in the Near-Infrared Regime - Abbaszadehbanaeiyan, Amin (My University, 2011)
Vertical-cavity surface-emitting lasers (VCSELs) have been considered as one of the promising candidates for today’s high speed communication systems. Small size, high data transmission rates, capability of achieving high production yields out of 2D array-based structures and wavelength tunability are some of the outstanding features of the VCSELs. Currently, there is a great deal of research on tunable VCSELs and these devices are believed to become the key components of the future optical networks. Microelectromechanical systems (MEMS) are one of the most successful technologies being utilized to obtain wide wavelength tuning ranges with the tunable VCSELs. In this master thesis a wavelength tunable MEMS-VCSEL operating at the central wavelength of 850 nm has been designed and fabricated for applications in wavelength division multiplexed (WDM) reconfigurable optical interconnects. The fabrication technology followed a hybrid integration of curved micro-mirrors on GaAs-based half-VCSEL chips in a one-chip approach. The gain medium of the laser consisted of five GaAs quantum wells and the bottom AlxGa1-xAs/AlyGa1-xAs DBR was grown epitaxially. Six highly p-doped current spreading layers were grown on top of the active region to enhance the current flow. Spherical photoresist structures were utilized as the sacrificial layer and titanium oxide (TiO2) / silicon oxide (SiO2) pure dielectric materials were deposited by DC and RF sputtering techniques to compose the MEMS distributed Bragg reflector (DBR). After surface micromachining and critical point drying (CPD) steps suspended MEMS mirrors were realized. From MATLAB simulations the reflectivity of the top 7.5-pair DBR was found to be around 99.9% with a full-width at half-maximum (FWHM) bandwidth of 320 nm. The final device had a foot print of 230 μm × 370 μm and consisted of a curved micro-mirror supported by four suspension beams, placed carefully on the 15-μm current aperture of the half-VCSEL chip. A transverse multi-mode behavior was observed in the MEMS-VCSEL device and the laser showed a threshold current around 6 mA with the maximum output power of 1.7 mW. The wavelength of the laser was tuned by sourcing electric current through a Ni actuation network, patterned on top of the micro-mirrors. The maximum obtained tuning range was around 12 nm with MEMS current of 18 mA.
Keywords: Informations- och kommunikationsteknik; Optik; Fotonik; Information & Communication Technology; Optics; Photonics